1631b Risk factors for carpal tunnel syndrome – findings from the niosh upper extremity musculoskeletal disorder consortium. (24th April 2018) - Evanoff, BA; Eisen, E; Gerr, F; Burt, S; Hegmann, K; Silverstein, B; Garg, A; Dale, AM; Bao, S; Harris-Adamson, C; Kapellusch, J; Merlino, L; et al.
Abstract : Starting in 2000, six research groups from the USA were supported by NIOSH to perform large, prospective epidemiologic studies examining associations between workplace physical risk factors and upper limb musculoskeletal disorders. A total of 4321 workers at 55 employers/plants across a variety of hand-intensive industries were followed for up to six years. Individual workplace exposure data included direct observation and video analysis. Health data included self-report, physical examination, and nerve conduction measures; our case definition for carpal tunnel syndrome (CTS) required both typical symptoms and nerve conduction abnormalities. Those performing the physical examinations and the video analyses were blinded to exposure and medical condition, respectively. Pooled analyses of consortium data controlled for personal factors (age, body mass index, gender, co-morbid diseases) and non-overlapping physical exposures (force, posture repetition) to study the association between work exposures and carpal tunnel syndrome. We found no independent effects of wrist posture or total repetition rate on the incidence of CTS. In contrast, strong dose-dependent associations were found between incident CTS and peak hand force (Borg CR10 > 3), forceful repetition rate (>3 exertions per minute of > 9N pinch force or 45N power grip), and the proportion of time spent in forceful exertion (>11%). We also found that the ACGIH Threshold Limit Value for Hand Activity (TLV for HAL) predicted CTS, and that that current 'action limit' is too high to adequately protect workers. Varying the formula of the TLV to emphasise force over repetition better predicted incident CTS. Study findings suggest that efforts to reduce workplace exposures should focus on jobs requiring high hand force and repeated or prolonged forceful exertions. Our study also suggests that the TLV for HAL and other less labour intensive assessment methods are valid and usable tools for workplace prevention.